Electrical properties of spin coated ultrathin titanium oxide films on GaAs. (16th April 2015) - Dutta, Shankar; Pal, Ramjay; Chatterjee, Ratnamala
Abstract: In recent years, ultrathin (<50 nm) metal oxide films have been being extensively studied as high- k dielectrics for future metal oxide semiconductor (MOS) technology. This paper discusses deposition of ultrathin TiO2 films (∼10 nm) on GaAs substrates (one sulfur-passivated, another unpassivated) by spin coating technique. The sulfur passivation is done to reduce the surface states of GaAs substrate. After annealing at 400 °C in a nitrogen environment, the TiO2 films are found to be polycrystalline in nature with rutile phase. The TiO2 films exhibit consistent grain size of 10–20 nm with thickness around 10–12 nm. Dielectric constants of the films are found to be 65.4 and 47.1 corresponding to S-passivated and unpassivated substrates, respectively. Corresponding threshold voltages of the MOS structures are measured to be −0.1 V to −0.3 V for the S-passivated and unpassivated samples, respectively. The S-passivated TiO2 film showed improved (lower) leakage current density (5.3 × 10 −4 A cm −2 at 3 V) compared to the unpassivated film (1.8 × 10 −3 A/cm 2 at 3 V). Dielectric breakdown-field of the TiO2 films on S-passivated and unpassivated GaAs samples are found to be 8.4 MV cm −1 and 7.2 MV cm −1 respectively.